PERSEPSI DAN PRAKTIK PENDIDIKAN KEBERLANJUTAN DI INDONESIA UNTUK EDUCATION FOR SUSTAINABILITY DEVELOPMENT (ESD) SELAMA PANDEMI COVID-19 - Nugroho, Oktian Fajar; Permanasari, Anna; Firman, Harry; Riandi, Riandi (Universitas Esa Unggul, 2021)
Education for Sustainable Development (ESD) has practical challenges, frequently linked to a restricted concept of sustainable literacy. This study investigates the effect of COVID-19 on sustainability literate views and practices using an educational symposium that detects changes in attitudes and practices of sustainability. This research investigates how disruption of pandemics might influence people and organizations. By comparing past global environmental restructuring plans with personal, professional and societal developments. Conceptions on sustainability and practice have modified the influence of COVID 19 on learning. The results demonstrate that the advantages of the epidemic have improved educators' thinking and increased their will for change by using the social networks of the educational community to promote collective action. Keywords: Education for Sustainable Development (ESD) , covid19, perceptions’ and activities’ pre-service